Masalah Kusta dan Diskriminasi Serta Stigmatisasinya di Indonesia - Tarigan, Nuah Perdamenta (Bina Nusantara University, 2013)
By developing an understanding on leprosy issues in social-community perspective, we will be more understanding to leprosy and many others. This is still a paramount in developing and building character especially in leadership context in modern Indonesia society. Good Interpersonal relationship always starts from self awareness, and then it could be developing among the men and women especially marginalized people in our society. Finally we could eliminate stigma and discrimination for people affected by leprosy promptly. The writer used the qualitiative method, with the aim of this research focuses on how to develop Nation Character Building based on our Founding Fathers Vision and make it down to earth to be our daily habits, appreciating and fair enough for every people and avoiding stigma and discrimination to anyone including people with disability and people affected by leprosy.